Hgh, EPO, anabolic steroids, and testosterone in swimming - Rushall, B. S. (Swimming Science Bulletin, 1998)
This article briefly covers human growth hormone (hGH), erythropoietin (EPO), and androgenic anabolic steroids and testosterone, and their potential for improving swimming performances. Knowing the potential of these particular substances (hereafter called "drugs") will allow swimmers, parents, coaches, and officials to more effectively monitor swimmers' behaviors for signs of this destructive practice. Closure: A problem with testing for hGH, EPO, and anabolic steroids and testosterone is that each is very different to the others. A unique strategic research and test-development approach is warranted. A scientist knowledgeable about steroids and testosterone might know little about the other substances. Steroids and testosterone are present in urine in much greater quantities for longer periods of time than either hGH or EPO. The small steroid molecules are more suited to mass spectrometry than the larger molecules of EPO or hGH. Although hGH, EPO, and anabolic steroids and testosterone are commonly discussed in swimming circles, only anabolic steroids and testosterone seem capable of direct performance enhancement. The best controls appear to be independent surprise testing. Research has shown that the more likely is surprise testing, the less is the use of banned substances. The best time for surprise testing is in the three months prior to major competitions when cheats try to use anabolic steroids or testosterone as close to the competition as possible.